(untitled) (Journal of the College of Basic Education, 2026)
The Arabic Letter has with witnessed a new development through its use in design, and its concepts as a formative element were formed from what was familiar and common before, where the contemporary designer. approached it in a new way 9 and was able to reveal its aesthetic dimensions and multiple capabilities that confirmed his artistic energies, investing in industry and technology to open new horizons for innovation and produce fabrics adorned with his compositions. The research contained four chapters. The first chapter included the research problem, its importance and its objective, in addition to defining the most important terms. The second chapter included the theoretical framework, which was divided into three sections: First: The get calligraphic school. Second: The Arabic letter and its role in design achievements, Third: Considerations for employing the Arabic letter in fabric designs. The third chapter included the research procedures and relied on the descriptive analytical approach. In the fourth and final chapter, the most important results, conclusions. recommendations and proposals were included.